Les verbes à objets cognats en portugais européen: quelques réflexions sur la conversion et la génération de mots - Choupina, Celda Morgado (2017)
The text analyzes the verbs with cognate objects in European Portuguese and provides an analysis of this phenomenon in the framework of Distributed Morphology, and a few ideas of the Minimalist Program. In this paper we only develop the analysis of the constructions of the type of chorar um choro... [cry a cry…] and cantar uma cantiga [sing a song]. Since a lexicalist theory as the one developed by Hale & Keyser (1993; 2002) can’t solve all the issues raised by the various types of constructions in EP, we will try any analysis that combines the contributions of Haugen (2009), on cognate objects, Marantz (1993) and Alexiadou (2001, 2006), on verbal functional heads, and (Chomsky 1995), on the idea of movement by copy.